2007
DOI: 10.1097/ijg.0b013e31803bbb17
|View full text |Cite
|
Sign up to set email alerts
|

Can Frequency-doubling Technology and Short-wavelength Automated Perimetries Detect Visual Field Defects Before Standard Automated Perimetry in Patients With Preperimetric Glaucoma?

Abstract: FDT and SWAP detect functional losses in cases of suspected glaucoma before glaucomatous losses detected by SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 57 publications
0
42
0
7
Order By: Relevance
“…Numerous studies [17][18][19][20][21][22][23][24] have reported the sensitivity and specificity of different versions of SLP for discriminating between healthy and glaucomatous eyes. Very few studies [25][26][27][28] however have tried to combine SLP variables to obtain an LDF to increase the diagnostic accuracy of isolated GDx-VCC-provided parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies [17][18][19][20][21][22][23][24] have reported the sensitivity and specificity of different versions of SLP for discriminating between healthy and glaucomatous eyes. Very few studies [25][26][27][28] however have tried to combine SLP variables to obtain an LDF to increase the diagnostic accuracy of isolated GDx-VCC-provided parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A low value represents low modulation and is associated with RNFL loss. Unfortunately, the normalized inferior area is not included in the standard printout, even though several studies 20,23 have reported that this parameter can provide a good ability to detect changes of the RNFL.…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, SWAP may detect functional deficits up to 5 years earlier than SAP in some patients [32,33]. In addition, in many cases, defects detected by SWAP correlate with early structural glaucomatous damage [34,35]. Moreover, some longitudinal studies suggest that SWAP may provide a better predictor of photographically-determined structural change than SAP [36, 37 • , 38].…”
Section: Short Wavelength Automated Perimetrymentioning
confidence: 99%
“…Other modes of testing which involve motion detection, frequency-doubling technology (FDT) and short-wavelength automated parameterizes (SWAP) detect visual field defects before standard automated perimetry in patients with preperimetric glaucoma and may enable earlier diagnosis. 29,31 In a report by the American Academy of Ophthalmology, 32 the four automated perimetry techniques that were assessed were short wavelength automated perimetry (SWAP), frequency doubling technology perimetry (FDT), high-pass resolution perimetry (HPRP), and motion automated perimetry (MAP). The algorithms described were the Swedish interactive threshold algorithm (SITA) and SITA fast.…”
Section: Evaluation Of the Visual Fieldmentioning
confidence: 99%